(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
An essential part of the logging in Bulgaria is done by private logging companies. From their active participation in the public procurement tenders, from their supplies of personnel and the presence of technical and transport vehicles largely depends on the planned logging – with high quality and in the right time. The peculiarities of the terrain and the different types and maturity plantations, the size of areas designated for logging and other factors cause variations in economic parameters, which they accomplish in different regions of the country. To achieve a reasonable balance between the interests of the owner of forests and the user, these differences must be analyzed, which is devoted to this study.